Structural brain abnormalities in postural tachycardia syndrome: A VBM-DARTEL study - Umeda, Satoshi; Harrison, Neil A.; Gray, Marcus A.; Mathias, Christopher J.; Critchley, Hugo D. (Frontiers in Neuroscience, 2015)
Postural tachycardia syndrome (PoTS), a form of dysautonomia, is characterized by orthostatic intolerance, and is frequently accompanied by a range of symptoms including palpitations, lightheadedness, clouding of thought, blurred vision, fatigue, anxiety and depression. Although the estimated prevalence of PoTS is approximately 5-10 times as common as the better-known condition orthostatic hypotension, the neural substrates of the syndrome are poorly characterized. In the present study, we used magnetic resonance imaging (MRI) with voxel-based morphometry (VBM) applying the diffeomorphic anatomical registration through exponentiated lie algebra (DARTEL) procedure to examine variation in regional brain structure associated with PoTS. We recruited eleven patients with established PoTS and twenty-three age-matched normal controls. Group comparison of grey matter volume revealed diminished grey matter volume within the left anterior insula, right middle frontal gyrus and right cingulate gyrus in the PoTS group. We also observed lower white matter volume beneath the precentral gyrus and paracentral lobule, right pre- and post-central gyrus, paracentral lobule and superior frontal gyrus in PoTS patients. Subsequent ROI analyses revealed significant negative correlations between left insula volume and trait anxiety and depression scores. Together, these findings of structural differences, particularly within insular and cingulate components of the salience network, suggest a link between dysregulated physiological reactions arising from compromised central autonomic control (and interoceptive representation) and increased vulnerability to psychiatric symptoms in PoTS patients.